Manipulation of product distributions via reverse flow operation with side feeding - Yogi W Budhi (Jurnal Teknik Kimia Indonesia, 2007)
A new concept of a reverse flow reactor with side feeding is studied for NH3 oxidation to produce N2, NO, and N2O. In the conventional reverse flow operation, where the feeds are alternately introduced from either end of the reactor, the conversion always decreases when compared to steady state, once through operation. The new concept of reverse flow operation with sidefeeding is therefore proposed to avoid the drop of conversion. The reactor behavior is simulated for three regimes (quasi-steady state, dynamic, sliding) with varying feed positions. The development of spatia-temporal patterns inside the reactor with side feeding shows completely different behavior compared to conventional reverse flow, leading to the possibility of conversion and selectivity manipulations.Keywords: Ammonia oxidation, Conversion and selectivity improvement, Reverse flow reactor, Side feedingAbstrakSuatu konsep baru dari reaktor aliran balik dengan pengumpanan samping telah dipelajari dengan kasus oksidasi NH3 untuk menghasilkan N2, NO, dan N2O. . Pada operasi aliran balik konvensional dimana umpan secara bergantian dimasukkan dari ujung reaktor, konversi yang dihasilkan selalu menunjukkan penurunan ketika dibandingkan dengan keadaan tunaknya dalam satu tahap operasi. Konsep baru aliran balik dengan pengumpanan samping dimaksudkan untuk menghindari penurunan konversi. Perilaku reaktor disimulasi dalam 3 rejim aliran (quasi-steady state, dynamic, sliding) dengan memvariasikan posisi umpan. Pembentukkan pola spatia-temporal di dalam reaktor dengan pengumpanan samping menunjukkan perilaku yang berbeda dibanding aliran balik konvensional. Hal ini memungkinkan untuk memanipulasi konversi dan selektivitas.Kata Kunci: Oksidasi Ammoniak, Pengumpanan  Samping, Peningkatan Konversi dan Selektivitas, Reaktor aliran bolak-balik